2015
DOI: 10.1007/978-3-319-18173-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Stochastic Submodular Maximization: Adaptive vs. Non-adaptive vs. Offline

Abstract: We consider the problem of stochastic monotone submodular function maximization, subject to constraints. We give results on adaptivity gaps, and on the gap between the optimal offline and online solutions. We present a procedure that transforms a decision tree (adaptive algorithm) into a non-adaptive chain. We prove that this chain achieves at least τ times the utility of the decision tree, over a product distribution and binary state space, where τ = min i,j Pr[x i = j]. This proves an adaptivity gap of 1 τ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…It was shown that there is a non-adaptive algorithm that achieves an approximation ratio of 1/3 with respect to an optimal adaptive algorithm. In [31], the problem of stochastic submodular maximization was also studied under various types of constraints, including knapsack constraints. An approximation ratio of τ for this problem under knapsack constraint was given, where τ is the smallest probability of any element in the ground set being realized by any item.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that there is a non-adaptive algorithm that achieves an approximation ratio of 1/3 with respect to an optimal adaptive algorithm. In [31], the problem of stochastic submodular maximization was also studied under various types of constraints, including knapsack constraints. An approximation ratio of τ for this problem under knapsack constraint was given, where τ is the smallest probability of any element in the ground set being realized by any item.…”
Section: Related Workmentioning
confidence: 99%
“…All except the orienteering results rely on having relaxations that capture the constraints of the problem via linear constraints. For stochastic monotone submodular functions where the probing constraints are given by matroids, Asadpour et al [AN16] bounded the adaptivity gap by e e´1 ; Hellerstein et al [HKL15] bound it by 1 τ , where τ is the smallest probability of some set being materialized. Other relevant papers are [LPRY08,DHK14].…”
Section: Further Related Workmentioning
confidence: 99%
“…For stochastic monotone submodular functions where the probing constraints are given by matroids, Asadpour et al [4] bounded the adaptivity gap by e e−1 ; Hellerstein et al [32] bound it by 1 τ , where τ is the smallest probability of some set being materialized. (See also [37,19].…”
Section: Related Workmentioning
confidence: 99%